The impact of job referrals on employment outcomes in top corporate positions - Lorenzo Maria Levati; Marie Lalanne (Leibniz Institute for Financial Research SAFE, 2020)
Using an original dataset on professional networks of directors sitting on the boards of large US corporations, we examine how personal relationships are used by firms to improve job match quality in the high-skill segment of the labor market. Analyzing explicit social connection data between new hires and recruiters, we are able to test predictions of well established job referral models. We find that referred executive directors have a fifteen percent longer tenure than their non-referred counterparts. Referred executive directors also tend to be similar to their referrers on multiple dimensions, giving support to network homophily hypotheses.
urn:nbn:de:hebis:30:3-530984
Keywords: L14; J63; M51; 330; Referrals; Job Match Quality; Social Networks; Board of Directors